Theory of the correlation between capillary and free-flow zone electrophoresis and its use for the conversion of analytical capillary separations to continuous free-flow preparative processes. Application to analysis and preparation of fragments of insulin - Kasicka, V; Prusík, Z; Sázelová, P; Jirácek, J; Barth, T (Journal of chromatography. A, 1998)
A basic theoretical description of the correlation between capillary zone electrophoresis (CZE) and free-flow zone electrophoresis (FFZE) is presented. The theory of the correlation between CZE and FFZE results from the fact that both methods are based on the same separation principle, zone electrophoresis, and both are performed in the carrierless separation medium with the same composition of the background electrolyte. The equations describing the movement of the charged and noncharged particles in the d.c. electric field applied in the capillary and in the flow-through electrophoretic chamber are presented and used for the quantitative description of the correlation between CZE and FFZE. Based on the theory of the correlation between CZE and FFZE a procedure has been developed for conversion of analytical, microscale CZE separations into continuous preparative separation processes realized by FFZE. Practical application of the developed procedure is demonstrated by CZE analysis and FFZE preparation of an octapeptide fragment of human insulin.
Keywords: Oligopeptides; Insulin; Chromatography, High Pressure Liquid; Electrophoresis, Capillary; lidé; inzulin; elektroforéza kapilární; chemické modely; oligopeptidy; Humans; Models, Chemical; vysokoúčinná kapalinová chromatografie